High-resolution seismic imaging reveals infill history of a submerged Quaternary fjord system in the subantarctic Auckland Islands, New Zealand. Issue 1 (January 2020) - Perkins, Edward J.; Gorman, Andrew R.; Tidey, Emily J.; Wilson, Gary S.; Ohneiser, Christian; Moy, Christopher M.; Riesselman, Christina R.; Gilmer, Greer; Ross, Ben S.
Abstract: Quaternary processes and environmental changes are often difficult to assess in remote subantarctic islands due to high surface erosion rates and overprinting of sedimentary products in locations that can be a challenge to access. We present a set of high-resolution, multichannel seismic lines and complementary multibeam bathymetry collected off the eastern (leeward) side of the subantarctic Auckland Islands, about 465 km south of New Zealand's South Island. These data constrain the erosive and depositional history of the island group, and they reveal an extensive system of sediment-filled valleys that extend offshore to depths that exceed glacial low-stand sea level. Although shallow, marine, U-shaped valleys and moraines are imaged, the rugged offshore geomorphology of the paleovalley floors and the stratigraphy of infill sediments suggests that the valley floors were shaped by submarine fluvial erosion, and subsequently filled by lacustrine, fjord, and fluvial sedimentary processes.